Analisa Penampang Balok Beton Bertulang Terhadap Variasi Jenis Keruntuhan - Aryanti, Riza (Jurnal Bangunan, Konstruksi & Desain, 2025)
Reinforced concrete beams are important structural elements in building construction that function to withstand bending and transverse loads. One crucial aspect in beam design is the proportion between the tensile capacity of the reinforcing steel and the compressive capacity of the concrete in the beam cross-section, which determines the type of failure that may occur, namely under reinforced, balanced reinforced, and over reinforced. Understanding the behavior of each type of failure is very important in the process of designing reinforced concrete structures to ensure safety and material efficiency. Therefore, in this study, cross-section analysis was conducted with a variation of the three types of failure through an analytical approach to the cross-section. Calculations were carried out with the help of RCCSA software. The results of the study in the form of moments and curvatures, loads and deflections, strain distribution and concrete stress distribution show that the under reinforced type of failure is the best for designing reinforced concrete beams.